2002
DOI: 10.2151/jmsj.80.119
|View full text |Cite
|
Sign up to set email alerts
|

Regime Shifts Found in the Northern Hemisphere SST Field.

Abstract: A 'regime shift' is characterized by an abrupt transition from one quasi-steady climatic state to another, and its transition period is much shorter than the lengths of the individual epochs of each climatic state. In the present study, we investigate when regime shifts occurred and what was the difference in climatic states before and after the shifts, using the wintertime sea surface temperature (SST) field in the Northern Hemisphere. The relationship between changes in the SST field, and those in the atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
89
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 35 publications
(41 reference statements)
10
89
0
1
Order By: Relevance
“…Significant changes appearing widely in the global SST anomaly field were found five times from the 1910s to the 1990s, which is consistent with the NH regime shifts already reported by previous studies (Overland et al, 1999;Yasunaka and Hanawa, 2002). It was also found that all the regime shifts happened concurrently with the ENSO events.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Significant changes appearing widely in the global SST anomaly field were found five times from the 1910s to the 1990s, which is consistent with the NH regime shifts already reported by previous studies (Overland et al, 1999;Yasunaka and Hanawa, 2002). It was also found that all the regime shifts happened concurrently with the ENSO events.…”
Section: Discussionsupporting
confidence: 91%
“…The regime shifts detected here are consistent well with the NH regime shifts already reported by previous studies (Overland et al, 1999;Yasunaka and Hanawa, 2002). In particular, the 1976-77 shift has been noted and described by many studies (e.g.…”
Section: Detection Of Global Regime Shiftssupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, some studies have examined the origin of the North Pacific regime shift in the winter of 1988/1989, arguing that this regime shift in the North Pacific is not very related to the tropical SST forcing, unlike the 1976/1977 climate regime shift [Tanaka et al, 1996;Walsh et al, 1996;Overland et al, 1999;Watanabe and Nitta, 1999;Hare and Mantua, 2000;Yasunaka and Hanawa, 2002;Yeh et al, 2011]. To be specific, the mean SST change in the North Pacific in the winter of 1988/1989 regime shift was not accompanied with a change in the mean SST in the tropical Pacific.…”
Section: Introductionmentioning
confidence: 99%